Shifting Paradigms: Exploring the Reasons for Staff Care and ‘The Duty of Care’ in International Peace and Conflict Work - Pastoors, Daniela (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Peace and conflict workers, peace educators and other humanitarian, aid and social workers are engaged in responsible and challenging contexts. There are a lot of reasons, why they should be accompanied, supported and counseled during their work - regardless of whether they are local or international staff, working in peace education, in the field of social justice, human rights or peacebuilding. The work of conflict workers and peace educators consists in fostering a culture of peace, which is closely connected to a culture of care.